2012
DOI: 10.36076/ppj.2012/15/421
|View full text |Cite
|
Sign up to set email alerts
|

Multivariate Prognostic Modeling of Persistent Pain Following Lumbar Discectomy

Abstract: Background: Persistent postsurgical pain (PPSP) affects between 10% and 50% of surgical patients, the development of which is a complex and poorly understood process. To date, most studies on PPSP have focused on specific surgical procedures where individuals do not suffer from chronic pain before the surgical intervention. Individuals who have a chronic nerve injury are likely to have established peripheral and central sensitization which may increase the risk of developing PPSP. Concurrent analyses of the po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
97
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(98 citation statements)
references
References 46 publications
0
97
1
Order By: Relevance
“…Lubelski et al and McGirt et al were deemed to have high ROB for the analysis domain because they used list-wise deletion with participants who had missing data [3••, 23]. Hegarty and Shorten et al also received a high ROB for the analysis domain because of a small sample size and had no mention of the statistical methods that were used for participants with missing data [24]. The other unmentioned studies scored low for the analysis domain.…”
Section: Risk Of Biasmentioning
confidence: 99%
See 1 more Smart Citation
“…Lubelski et al and McGirt et al were deemed to have high ROB for the analysis domain because they used list-wise deletion with participants who had missing data [3••, 23]. Hegarty and Shorten et al also received a high ROB for the analysis domain because of a small sample size and had no mention of the statistical methods that were used for participants with missing data [24]. The other unmentioned studies scored low for the analysis domain.…”
Section: Risk Of Biasmentioning
confidence: 99%
“…We included studies in patients undergoing cervical spine (n = 3), thoracolumbar spine (n = 2), and lumbar spine (n = 8) surgery [3••, 5••, 6••, [23][24][25][26][27][28][29][30][31][32]. These studies reported predictive models (n = total number of models) to estimate post-surgical patient-reported outcomes of the following: return to work (n = 3), pain (n = 9), physical functioning and disability (n = 5), quality of life (QOL) (n = 6), and psychosocial disposition (n = 2) reported in Table 4.…”
Section: Predicted Patient-reported Outcomes By Spine Regionmentioning
confidence: 99%
“…org Patient-centred outcome prediction is a growing focus in spine research, producing several reports annually. The majority discuss prediction in terms of Patient-Reported Outcome Measures (PROMs) [5][6][7][8][9][10][11][12][13][14][15], a few deals with adverse events [16,17], length of stay [18], revision surgery [19] or return to work [20]. Among the PROM analyses, the outcome measure is usually dichotomized.…”
Section: Introductionmentioning
confidence: 99%
“…Both age (Deyo et al., 2010; Hagg, Fritzell, Ekselius, & Nordwall, 2003; Hegarty & Shorten, 2012) and gender (Deyo et al., 2010; Hegarty & Shorten, 2012) could influence short‐ and long‐term outcomes of pain and function and are significant predictors of health care utilization following LSS (Deyo et al., 2010; Hagg et al., 2003; Hegarty & Shorten, 2012). Perruccio, Gandhi, and Rampersaud (2013) reported an association between pain scores, age, and gender among hip and knee musculoskeletal disorders.…”
Section: Introductionmentioning
confidence: 99%